Penyuluhan Masyarakat Mengenai Internet Sehat Di Desa Batulayang Bogor - Sri Hartanto (LP3M Universitas Putra Bangsa, 2025)
The public needs to know about safe and healthy use of the internet so that it can prevent harm to the public when accessing the internet. The public needs to be educated about security threats when using the internet, which are generally caused by viruses and phishing on the telecommunications devices they use, such as smartphones, tablets, or computers. Viruses are programs that can spread via the internet to damage the systems of the telecommunications equipment used. Meanwhile, phishing is a fake link in the name of an agency or organization to direct victims to a fake login page as a trap to steal personal data. Therefore, to educate the public about safe and healthy use of the internet, community outreach was held in Batulayang Village, Bogor. The material focused on recognizing the threat of viruses and phishing on the internet. By carrying out outreach about the threat of viruses and phishing in community service in Batulayang Village, Bogor, it is hoped that the community will better understand and be aware of the threat of viruses and phishing so that people in Batulayang Village, Bogor, will be more concerned and alert when using the internet.